Maternal Low-Protein Diet Deregulates DNA Repair and DNA Replication Pathways in Female Offspring Mammary Gland Leading to Increased Chemically Induced Rat Carcinogenesis in Adulthood - Zapaterini, Joyce R.; Fonseca, Antonio R. B.; Bidinotto, Lucas T.; Colombelli, Ketlin T.; Rossi, André L. D.; Kass, Laura; Justulin, Luis A.; Barbisan, Luis F. (Frontiers in Cell and Developmental Biology, 2022)
Studies have shown that maternal malnutrition, especially a low-protein diet (LPD), plays a key role in the developmental mechanisms underlying mammary cancer programming in female offspring. However, the molecular pathways associated with this higher susceptibility are still poorly understood. Thus, this study investigated the adverse effects of gestational and lactational low protein intake on gene expression of key pathways involved in mammary tumor initiation after a single dose of N-methyl-N-nitrosourea (MNU) in female offspring rats. Pregnant Sprague–Dawley rats were fed a normal-protein diet (NPD) (17% protein) or LPD (6% protein) from gestational day 1 to postnatal day (PND) 21. After weaning (PND 21), female offspring (n = 5, each diet) were euthanized for histological analysis or received NPD (n = 56 each diet). At PND 28 or 35, female offspring received a single dose of MNU (25 mg/kg body weight) (n = 28 each diet/timepoint). After 24 h, some females (n = 10 each diet/timepoint) were euthanized for histological, immunohistochemical, and molecular analyses at PDN 29 or 36. The remaining animals (n = 18 each diet/timepoint) were euthanized when tumors reached ≥2 cm or at PND 250. Besides the mammary gland development delay observed in LPD 21 and 28 groups, the gene expression profile demonstrated that maternal LPD deregulated 21 genes related to DNA repair and DNA replication pathways in the mammary gland of LPD 35 group after MNU. We further confirmed an increased γ-H2AX (DNA damage biomarker) and in ER-α immunoreactivity in mammary epithelial cells in the LPD group at PND 36. Furthermore, these early postnatal events were followed by significantly higher mammary carcinogenesis susceptibility in offspring at adulthood. Thus, the results indicate that maternal LPD influenced the programming of chemically induced mammary carcinogenesis in female offspring through increase in DNA damage and deregulation of DNA repair and DNA replication pathways. Also, Cidea upregulation gene in the LPD 35 group may suggest that maternal LPD could deregulate genes possibly leading to increased risk of mammary cancer development and/or poor prognosis. These findings increase the body of evidence of early-transcriptional mammary gland changes influenced by maternal LPD, resulting in differential response to breast tumor initiation and susceptibility and may raise discussions about lifelong prevention of breast cancer risk.